Bilingualism as an educational public policy. Elements contemplated in the Colombian regulatory framework - Saurith Ropain, Iliana (2023)
The objective of the research was to identify the elements of the public policy of the higher education sector oriented to bilingualism. Methodologically, it is a study with a qualitative approach of documentary type, whose unit of analysis was the set of documents containing the public policy of bilingualism; being the population those instruments aimed at the university sector, and within these the units of observation: Political Constitution of Colombia 1991, Law 30 of 1992, Law 1651 of 2013, Decree 1330 of 2019. The findings allowed identifying four major elements of public policy in the regulatory framework: 1. Obligation and satisfaction of educational needs, 2. Promotion of science and other expressions through comprehensive training, 3. Promotion of internationalization, and 4. Evaluation of higher education, the same were defined in the framework of their content and relationship with the aforementioned policy, also disaggregated into indicators with a view to continuing the line of research in the future. We conclude on the need to analyze these elements identified in the Colombian university reality in order to offer possible answers to the results achieved so far with the implemented bilingual public policy, which do not seem to satisfy the objectives proposed by governmental agencies and educational institutions.